Composites of Graphene and LiFePO4 as Cathode Materials for Lithium-Ion Battery: A Mini-review - Wu, Haixia; Liu, Qinjiao; Guo, Shouwu (Nano-Micro Letters, 2014)
This mini-review highlights selectively the recent research progress in the composites of LiFePO4 and graphene. In particularly, the different fabrication protocols, and the electrochemical performance of the composites are summarized in detail. The structural and morphology characters of graphene sheets that may affect the property of the composites are discussed briefly. The possible ongoing researches in area are speculated upon.